2016
DOI: 10.1097/sla.0000000000001660
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Versus Open Pancreatoduodenectomy

Abstract: Outcomes after MIPD seem promising in comparative cohort studies, despite the presence of bias, whereas registry studies report higher mortality in low-volume centers. The introduction of MIPD should be closely monitored and probably done only within structured training programs in high-volume centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(77 citation statements)
references
References 70 publications
1
58
0
9
Order By: Relevance
“…Laparoscopic pancreatoduodenectomy, although technically difficult and requiring a high degree of expertise, has shown efficacy equal to that of open pancreatoduodenectomy in terms of complications, oncological safety and overall outcomes, with inherent advantages of minimally invasive surgery such as decreased blood loss, reduced pain, shorter hospital stay and earlier return to work. Although a recent study from a high‐volume centre reported concerns about greater morbidity for the laparoscopic approach, with a higher pancreatic fistula rate, a meta‐analysis including more than 20 000 patients revealed favourable outcomes in well selected patients in centres with a larger volume.…”
Section: Introductionmentioning
confidence: 99%
“…Laparoscopic pancreatoduodenectomy, although technically difficult and requiring a high degree of expertise, has shown efficacy equal to that of open pancreatoduodenectomy in terms of complications, oncological safety and overall outcomes, with inherent advantages of minimally invasive surgery such as decreased blood loss, reduced pain, shorter hospital stay and earlier return to work. Although a recent study from a high‐volume centre reported concerns about greater morbidity for the laparoscopic approach, with a higher pancreatic fistula rate, a meta‐analysis including more than 20 000 patients revealed favourable outcomes in well selected patients in centres with a larger volume.…”
Section: Introductionmentioning
confidence: 99%
“…A sufficient extent of surgical resection and lymphadenectomy can be achieved by laparoscopic access, as proved by the pathological examination of the resection specimen showing a sufficient number of lymph nodes resected and negative resection margins. Blood loss was significantly lower compared to conventional methods (11,12). Operating time was slightly longer with laparoscopic procedures compared to the classical method and the number of post-operative days is lower in the laparoscopic compared to the conventional surgery (13).…”
Section: Discussionmentioning
confidence: 98%
“…Systematic reviews and meta-analyses comparing MIPD and OPD report less intraoperative blood loss, a lower transfusion rate, longer operative time, and shorter hospital stay for the former [42][43][44][45]. The oncologic outcomes were equivalent to those in OPD [41,45].…”
Section: Minimally Invasive Pancreatoduodenectomymentioning
confidence: 92%